Measuring food and service quality variation among food franchise chain outlets in Malaysia - Abd Rahman, Azmawani; Pun, Hui Si (2011)
Standardization in franchising system is very important to ensure all the services and products provide the same in terms of their service quality and product quality which will lead to customer satisfaction. This study investigates food and service quality variation among food franchise chain outlets. Findings the data collected from 150 customers indicate that franchising business format are not able to ensure the standardization of food and service quality amongst fast food chain Restaurant in Malaysia. Empirical evidence proves the existence of variations in terms of food and service quality among fast food franchise outlets. The study concludes that, although standardization is expected from the franchisee outlets, some outlets are not able to follow the same standards for products or services in the franchise system. The results of the study provide implication to the franchisee, franchisor, government body, and the body of knowledge in quality and franchising literature.